Semi-interpenetrating Network Membrane from Polyethyleneimine-Epoxy Resin and Polybenzimidazole for HT-PEM Fuel Cells - Chao Meng; Sheng Huang; Dongmei Han; Shan Ren; Shuanjin Wang; Min Xiao (Advances in Polymer Technology)
In the present work, a semi-interpenetrating network (semi-IPN) high-temperature proton exchange membrane based on polyethyleneimine (PEI), epoxy resin (ER), and polybenzimidazole (PBI) was prepared and characterized, aiming at their future application in fuel cell devices. The physical properties of the semi-IPN membrane are characterized by thermogravimetric analysis (TGA) and tensile strength test. The results indicate that the as-prepared PEI-ER/PBI semi-IPN membranes possess excellent thermal stability and mechanical strength. After phosphoric acid (PA) doping treatment, the semi-IPN membranes show high proton conductivities. PA doping level and volume swelling ratio as well as proton conductivities of the semi-IPN membranes are found to be positively related to the PEI content. High proton conductivities of 3.9∽7.8×10−2 S cm−1 are achieved at 160°C for these PA-doped PEI-ER/PBI series membranes. H2/O2 fuel cell assembled with PA-doped PEI-ER(1 : 2)/PBI membrane delivered a peak power density of 170 mW cm-2 at 160°C under anhydrous conditions.